ANALYSIS OF GRADE IX JUNIOR HIGH SCHOOL STUDENTS' MATHEMATICAL CONCEPTUAL UNDERSTANDING IN SOLVING QUADRILATERAL PROBLEMS - Desri Rizkia Nurfarihah; Indra Budiman; Dani Firmansyah (JME (Journal of Mathematics Education), 2026)
The purpose of this study was to describe the mathematical concept understanding of ninth-grade junior high school students in solving problems involving quadrilaterals. A quantitative descriptive method was used on a sample of 38 students. The research instrument consisted of an essay test based on indicators of concept understanding, including the ability to verbally restate concepts, classify objects, and present concepts in various forms of mathematical representation. The research results showed that students’ mathematical conceptual understanding fell into the moderate category with an average score of 72. Based on the grouping results, there were 11 students in the high category, 20 in the moderate category, and 7 in the low category. Students in the high category met most of the indicators, while students in the moderate and low categories still experienced difficulties, particularly with the mathematical representation indicator. Overall, students’ mathematical concept understanding was not uniform, so learning efforts are needed that place greater emphasis on strengthening concept understanding.